A case with catecholaminergic polymorphic ventricular tachycardia - Ahmet Ünalır (Journal of Clinical and Experimental Investigations, 2011)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare type of polymorphic ventricular tachycardias in individuals without structural cardiac abnormalities. It typically has been induced by exercise or emotional stres. It generally is seen in childhood and adolescent period but rarely is seen in elderly. It usually ends by spontaneus, but rarely cause hemodynamic collapse. In here, we present a case with CPVT of successful treatment with a beta blocker therapy. J Clin Exp Invest 2011;2(2):232-4